Development Research in Science Education: A Systematic Literature Review of Trends in Development Models and Instruments Used - Ratih Komala Dewi; Darmanella Dian Eka Wati; Oria Lasmana; Yerimadesi; Festiyed; Yuni Ahda; Heffi Alberida (Jurnal Penelitian Pendidikan IPA, 2024)
This study was motivated by the desire to know the trend of development models and instruments used in development research.  The purpose of this study was to conduct a comprehensive review of the existing literature on development research in science education. The focus was to identify trends in development models and instruments used in this field. This research is a type of systematic literature review using the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) method to look at trends in development models and instruments in science education development research. This research uses Scopus, Science Direct and Eric databases. The results of this study are the most widely used development model is the ADDIE development model and questionnaires are the instruments used in all articles analyzed.